Citra Perempuan dalam Novel Kekuatan Cinta karya Sastri Bakry - Arizona, Ria Defrita; Gani, Erizal; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this research is to describe the reflection of the woman characteristic in the novel Kekuatan Cinta by Sastri Bakri. Some theory that use in this research are: (1) the meaning of novel, (2) parts of novel, (3) the approach when understand literature, (4) the meaning of woman’s reflection, (5) the woman’s reflection as herself, (6) the reflectionof woman as a civil. This research is kind of qualitative research by using the core analysis approach. The aim of analyzing woman characteristic in the novel is to know the reflectionby main character. The result of this research shows that the reflection of the woman, Sas, as a strong woman through life.